Antibacterial easy-to-clean bathroom ceramic and preparation method thereof

By adding Ni1-xZnxCo2O4 and phytic acid-Ce3+ and Cu2+ composite materials to the glaze layer of the bathroom ceramics, and calcination treatment, the problem of insufficient antibacterial performance in the prior art is solved, excellent antibacterial performance and easy cleaning are achieved, and production costs are reduced.

CN119822642APending Publication Date: 2025-04-15GUANGDONG YUSHENG NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510067988.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art has shortcomings in antibacterial performance, especially when it does not rely on light conditions and does not add silver, it is difficult to achieve excellent antibacterial performance, and the production cost is high.

Method used

By adding Ni1-xZnxCo2O4 and phytic acid-Ce3+ and Cu2+ composites to the glaze layer of the bathroom ceramic, and cerium oxide and copper oxide are obtained by calcining treatment, the antibacterial properties of the ceramic are improved.

Benefits of technology

It realizes that the bathroom ceramics have excellent antibacterial properties and easy cleaning without relying on lighting conditions and adding silver, reducing production costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of ceramics, and particularly relates to an antibacterial easy-to-clean bathroom ceramic and a preparation method thereof. The antibacterial easy-to-clean bathroom ceramic comprises a bathroom ceramic green body and a glaze layer, and the glaze layer is prepared from the following raw materials in parts by weight: 70 to 90 parts of kaolin, 10 to 30 parts of baddeleyite, 20 to 40 parts of potassium feldspar, 5 to 15 parts of dolomite and 4 to 8 parts of Ni (1-x) ZnxCo2O4 (x is 0.03 to 0.05); 6-12 parts of a phytic acid-Ce < 3 + > and Cu < 2 + > composite material, 4-12 parts of polyvinyl alcohol and 50-70 parts of water. The antibacterial property of the ceramic can be improved by adding Ni1-xZnxCo2O4, the dispersion uniformity of Ce < 3 + > and Cu < 2 + > on a glaze layer can be improved by complexing Ce < 3 + > and Cu < 2 + > through phytic acid, cerium oxide and copper oxide are obtained through calcination treatment, the antibacterial property of the bathroom ceramic is further improved, and the obtained bathroom ceramic is easy to clean and excellent in antibacterial property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ceramics, and more specifically, relates to an antibacterial and easy-to-clean sanitary ceramic and a preparation method thereof. Background Art

[0002] As people's health awareness increases, antibacterial technology is widely used in sanitary ware products, and products with antibacterial functions have received widespread attention from consumers.

[0003] CN115594403A discloses an antibacterial easy-to-clean glaze and its sanitary ceramics and a preparation method of sanitary ceramics. The antibacterial easy-to-clean glaze is sprayed on the surface of the white glaze layer of the sanitary ceramics. The raw materials of the antibacterial easy-to-clean glaze include: quartz powder, wollastonite, potassium feldspar powder, nano zinc oxide antibacterial agent and silver ion antibacterial agent by mass percentage; the stacking ratio of particles with a particle size of 10 μm in the antibacterial easy-to-clean glaze is 70-90wt%; it has a long-term antibacterial effect, and the antibacterial easy-to-clean glaze after firing should form a layer of glassy glaze on the surface of the white glaze layer, and also has an easy-to-clean effect of cleaning dirt by washing with water. The preparation method of sanitary ceramics using the antibacterial easy-to-clean glaze for sanitary ceramics proposed by the present invention has simple equipment, convenient operation and good manufacturing cost. The sanitary ceramics using the antibacterial easy-to-clean glaze for sanitary ceramics proposed by the present invention have an antibacterial rate that meets the standard and has a good easy-to-clean effect.

[0004] CN106673633A discloses an antibacterial sanitary ceramic product and a preparation method thereof, comprising a body and a glaze, wherein the raw materials of the body are: talc, kaolin, calcium feldspar, bauxite, muscovite, ilmenite, wollastonite, chlorite, and silicon nitride; the raw materials of the glaze are: talc, calcium feldspar, borax, zirconium silicate, titanium dioxide, zinc oxide, and nano-silver; the preparation method comprises: crushing and sieving the raw materials of the body to obtain raw materials for the body; subjecting the raw materials for the body to wet ball milling, standing and aging, slip casting, demoulding, drying, and bisque firing to obtain a body; mixing and crushing talc, calcium feldspar and borax, adding nano-silver and dilute nitric acid, drying, and adding zirconium silicate, titanium dioxide and zinc oxide to obtain a glaze; subjecting the glaze to wet ball milling, standing and aging, and then spraying it on the surface of the body to obtain a product to be fired; and glaze firing the product to be fired to obtain the antibacterial sanitary ceramic product. The antibacterial sanitary ceramic product prepared by the invention has good weather resistance, antibacterial property and low water absorption rate.

[0005] In the prior art, antibacterial properties are achieved by adding photocatalysts or silver. Adding photocatalysts can only be antibacterial under light, while adding metallic silver will increase the production cost. Based on the above, the present invention provides an antibacterial and easy-to-clean sanitary ceramic with excellent antibacterial properties without adding silver under light conditions. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art and provide an antibacterial and easy-to-clean sanitary ceramic and a preparation method thereof. The antibacterial and easy-to-clean sanitary ceramic comprises a sanitary ceramic body and a glaze layer. The glaze layer comprises the following raw materials by weight: 70-90 parts of kaolin, 10-30 parts of baddeleyite, 20-40 parts of potassium feldspar, 5-15 parts of dolomite, Ni 1-x Zn x Co2O4, x = 0.03~0.05, 4~8 parts; phytic acid-Ce 3+ and Cu 2+ 6-12 parts of composite material, 4-12 parts of polyvinyl alcohol, and 50-70 parts of water. 1-x Zn x Co2O4 can improve the antibacterial properties of ceramics by complexing Ce with phytic acid 3+ and Cu 2+ , can improve Ce 3+ and Cu 2+ The uniform dispersion of the glaze layer is achieved by calcining to obtain cerium oxide and copper oxide, which further improves the antibacterial properties of sanitary ceramics. The obtained sanitary ceramics are easy to clean and have excellent antibacterial properties.

[0007] The purpose of the present invention is to provide an antibacterial and easy-to-clean sanitary ceramic.

[0008] Another object of the present invention is to provide a method for preparing antibacterial and easy-to-clean sanitary ceramics.

[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions: An antibacterial and easy-to-clean sanitary ceramic, comprising a sanitary ceramic body and a glaze layer, wherein the glaze layer comprises the following raw materials in parts by weight: Kaolin 70~90 parts, baddeleyite 10~30 parts, feldspar 20~40 parts, dolomite 5~15 parts, Ni 1- x Zn x Co2O4, x = 0.03~0.05, 4~8 parts; phytic acid-Ce 3+ and Cu 2+ 6-12 parts of composite material, 4-12 parts of polyvinyl alcohol (2000), and 50-70 parts of water.

[0010] According to a preferred technical solution, the particle sizes of the kaolin, baddeleyite, potassium feldspar and dolomite are all 30-70 μm.

[0011] In a further preferred embodiment, the Ni 1-x Zn x The preparation method of Co2O4 comprises the following steps: Nickel salt, zinc salt, cobalt salt and polyethylene glycol 2000 are added to ethylene glycol, ultrasonically dispersed for a certain period of time, and then subjected to solvent thermal reaction, cooled to room temperature, filtered, washed, dried, then ground and calcined to obtain Ni 1-x Zn x Co2O4.

[0012] Preferably, the nickel salt is one of nickel nitrate, nickel chloride, and nickel acetate; the zinc salt is one of zinc nitrate, zinc chloride, and zinc acetate; the cobalt salt is one of cobalt nitrate, cobalt chloride, and cobalt acetate; the ratio of the nickel salt, zinc salt, cobalt salt, and polyethylene glycol 2000 is (1-x) mol:x mol:2 mol, 200~240g, x=0.03~0.05.

[0013] Preferably, the ultrasonic dispersion time is 20-40 min; and the solvothermal reaction conditions are solvothermal reaction at 160-200° C. for 10-20 h.

[0014] Preferably, the drying is performed at 60-100° C. for 10-14 h; and the calcining is performed at 280-320° C. for 2-4 h.

[0015] In a further preferred embodiment, the phytic acid-Ce 3+ and Cu 2+ The preparation method of the composite material comprises the following steps: Sodium phytate, cerium salt and copper salt were ultrasonically dispersed in deionized water, stirred at room temperature for a certain period of time, filtered, washed and vacuum dried to obtain phytic acid-Ce 3+ and Cu 2+ Composite materials.

[0016] Preferably, the molar ratio of the sodium phytate, the cerium salt and the copper salt is 1:0.04~0.08:0.6~0.8, the cerium salt is one of cerium nitrate, cerium chloride and cerium acetate; the copper salt is one of copper nitrate, copper chloride and copper acetate.

[0017] Preferably, the stirring time is 2-4 hours; and the vacuum drying is performed at 60-80° C. for 14-20 hours.

[0018] Based on the above-mentioned method for preparing antibacterial and easy-to-clean sanitary ceramics, the preparation method comprises the following steps: 1) Preparation of bathroom ceramic embryos: 2) Place kaolin, baddeleyite, feldspar, dolomite and water in a ball mill and mix at a speed of 400-600 r / min for 2-6 hours; 3) Then Ni 1-x Zn x Co2O4, Phytate-Ce 3+ and Cu2+ The composite material and polyethylene glycol (2000) are added into the ball mill and the ball milling is continued for 10 to 30 minutes to obtain a glaze; 4) applying the glaze to the surface of the sanitary ware ceramic body in step 1), and drying naturally to obtain a glazed sanitary ware ceramic body; 5) The glazed sanitary ceramic body is heated from room temperature to 500-600° C. at a heating rate of 1-3° C. and kept at that temperature for 2-6 hours, then heated to 1200-1400° C. at a heating rate of 10-14° C. and sintered for 4-8 hours; cooled to 600-800° C. and kept at that temperature for 4-8 hours; and then cooled in the furnace to obtain an antibacterial and easy-to-clean sanitary ceramic body.

[0019] The present invention has the following beneficial effects: The present invention prepares zinc-doped nickel cobaltate antibacterial material. Due to the doping of cobalt, the nickel cobaltate has excellent antibacterial properties, thereby promoting the excellent antibacterial properties of sanitary ceramics. 3+ and Cu 2+ , can improve Ce 3+ and Cu 2+ The uniform dispersion of the glaze layer is achieved by calcining to obtain cerium oxide and copper oxide, which further improves the antibacterial properties of sanitary ceramics. The obtained sanitary ceramics are easy to clean and have excellent antibacterial properties. DETAILED DESCRIPTION

[0020] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0021] The particle sizes of the kaolin, baddeleyite, potassium feldspar and dolomite are all 50 μm.

[0022] Unless otherwise specified, the reagents and materials used in the following examples are commercially available. Example

[0023] An antibacterial and easy-to-clean sanitary ceramic, comprising a sanitary ceramic body and a glaze layer, wherein the glaze layer comprises the following raw materials in parts by weight: 80 parts of kaolin, 20 parts of baddeleyite, 30 parts of potassium feldspar, 10 parts of dolomite, Ni 0.96 Zn 0.04 Co2O4, 6 parts; Phytic acid-Ce 3+ and Cu 2+ 10 parts of composite material, 8 parts of polyvinyl alcohol (2000), and 60 parts of water.

[0024] The Ni 0.96 Zn 0.04The preparation method of Co2O4 comprises the following steps: 0.96 mol nickel nitrate, 0.04 mol zinc chloride, 2 mol cobalt nitrate and 220 g polyethylene glycol 2000 were added to 400 mL ethylene glycol, ultrasonically dispersed for 30 min, then solvothermally reacted at 180 ° C for 16 h, cooled to room temperature, filtered, washed, dried at 80 ° C for 12 h, then ground, and calcined at 300 ° C for 3 h to obtain Ni 0.96 Zn 0.04 Co2O4.

[0025] The phytic acid-Ce 3+ and Cu 2+ The preparation method of the composite material comprises the following steps: 1 mol of sodium phytate, 0.06 mol of cerium nitrate and 0.7 mol of copper acetate were ultrasonically dispersed in 200 mL of deionized water, stirred at room temperature for 3 h, filtered, washed, and vacuum dried at 70 ° C for 18 h to obtain phytic acid-Ce 3+ and Cu 2+ Composite materials.

[0026] The preparation method of the antibacterial easy-to-clean sanitary ceramic comprises the following steps: 1) Preparation of bathroom ceramic embryos: 2) Place kaolin, baddeleyite, feldspar, dolomite and water in a ball mill and mix at a speed of 500 r / min for 4 h; 3) Then Ni 0.96 Zn 0.04 Co2O4, Phytate-Ce 3+ and Cu 2+ The composite material and polyethylene glycol (2000) are added into the ball mill and ball milling is continued for 20 minutes to obtain a glaze; 4) applying the glaze to the surface of the sanitary ware ceramic body in step 1), and drying naturally to obtain a glazed sanitary ware ceramic body; 5) The glazed sanitary ceramic body is heated from room temperature to 550° C. at a heating rate of 2° C. and kept at that temperature for 4 hours, then heated to 1300° C. at a heating rate of 12° C. and sintered for 6 hours; cooled to 700° C. and kept at that temperature for 6 hours; and then cooled in the furnace to obtain the antifouling sanitary ceramic body. Example

[0027] An antibacterial and easy-to-clean sanitary ceramic, comprising a sanitary ceramic body and a glaze layer, wherein the glaze layer comprises the following raw materials in parts by weight: 90 parts of kaolin, 10 parts of baddeleyite, 40 parts of potassium feldspar, 5 parts of dolomite, Ni 0.95 Zn 0.05 Co2O4, 8 parts; Phytic acid-Ce 3+and Cu 2+ 6 parts of composite material, 12 parts of polyvinyl alcohol (2000), and 70 parts of water.

[0028] The Ni 0.95 Zn 0.05 The preparation method of Co2O4 comprises the following steps: 0.95 mol nickel nitrate, 0.05 mol zinc acetate, 2 mol cobalt chloride and 240 g polyethylene glycol 2000 were added to 400 mL ethylene glycol, ultrasonically dispersed for 40 min, then solvothermally reacted at 200 °C for 10 h, cooled to room temperature, filtered, washed, dried at 100 °C for 10 h, then ground, and calcined at 320 °C for 2 h to obtain Ni 0.95 Zn 0.05 Co2O4.

[0029] The phytic acid-Ce 3+ and Cu 2+ The preparation method of the composite material comprises the following steps: 1 mol sodium phytate, 0.08 mol cerium chloride and 0.6 mol copper acetate were ultrasonically dispersed in 200 mL deionized water, stirred at room temperature for 4 h, filtered, washed, and vacuum dried at 80 ° C for 14 h to obtain phytic acid-Ce 3+ and Cu 2+ Composite materials.

[0030] The preparation method of the antibacterial and easy-to-clean sanitary ceramic is the same as that in Example 1. Example

[0031] An antibacterial and easy-to-clean sanitary ceramic, comprising a sanitary ceramic body and a glaze layer, wherein the glaze layer comprises the following raw materials in parts by weight: 70 parts of kaolin, 30 parts of baddeleyite, 20 parts of potassium feldspar, 15 parts of dolomite, Ni 0.97 Zn 0.03 Co2O4, 4 parts; Phytic acid-Ce 3+ and Cu 2+ 12 parts of composite material, 4 parts of polyvinyl alcohol (2000), and 50 parts of water.

[0032] The Ni 0.97 Zn 0.03 The preparation method of Co2O4 comprises the following steps: 0.97 mol nickel chloride, 0.03 mol zinc nitrate, 2 mol cobalt acetate and 200 g polyethylene glycol 2000 were added to 400 mL ethylene glycol, ultrasonically dispersed for 20 min, then solvothermally reacted at 160 ° C for 20 h, cooled to room temperature, filtered, washed, dried at 60 ° C for 14 h, then ground, and calcined at 280 ° C for 4 h to obtain Ni0.97 Zn 0.03 Co2O4.

[0033] The phytic acid-Ce 3+ and Cu 2+ The preparation method of the composite material comprises the following steps: 1 mol sodium phytate, 0.04 mol cerium acetate and 0.8 mol copper nitrate were ultrasonically dispersed in 200 mL deionized water, stirred at room temperature for 2 h, filtered, washed, and vacuum dried at 60 ° C for 20 h to obtain phytic acid-Ce 3+ and Cu 2+ Composite materials.

[0034] The preparation method of the antibacterial and easy-to-clean sanitary ceramic is the same as that in Example 1.

[0035] Comparative Example 1 An equal amount of NiCo2O4 is used to replace the Ni in Example 1. 0.96 Zn 0.04 Co2O4, and the rest is the same as in Example 1. The preparation method of NiCo2O4 comprises the following steps: 1 mol of nickel nitrate, 2 mol of cobalt nitrate and 220 g of polyethylene glycol 2000 were added to 400 mL of ethylene glycol, ultrasonically dispersed for 30 min, then solvothermally reacted at 180 °C for 16 h, cooled to room temperature, filtered, washed, dried at 80 °C for 12 h, then ground, and calcined at 300 °C for 3 h to obtain NiCo2O4.

[0036] Comparative Example 2 Using equal parts of phytic acid-Cu 2+ Replace the phytic acid-Ce in Example 1 3+ and Cu 2+ , and the rest is the same as in Example 1. The phytic acid-Cu 2+ The preparation method of the composite material comprises the following steps: 1 mol of sodium phytate and 0.76 mol of copper acetate were ultrasonically dispersed in 200 mL of deionized water, stirred at room temperature for 3 h, filtered, washed, and vacuum dried at 70 ° C for 18 h to obtain phytic acid-Cu 2+ Composite materials.

[0037] Comparative Example 3 The phytic acid-Ce in Example 1 3+ and Cu 2+ The copper-cerium composite oxide is replaced with an equal amount, and the rest is the same as in Example 1. The preparation method of the copper-cerium composite oxide comprises the following steps: 0.06 mol of cerium nitrate and 0.7 mol of copper acetate are stirred evenly, then calcined at 550° C. for 4 hours, and ground to obtain the copper-cerium composite oxide.

[0038] Comparative Example 4 Using equal parts of Ni 0.96 Zn 0.04 Co2O4 replaces the phytic acid-Ce in Example 1 3+ and Cu 2+ , the rest is the same as Example 1.

[0039] The wear resistance and antibacterial properties of Examples 1-3 and Comparative Examples 1-4 were tested. The specific test results are shown in Table 1.

[0040] Among them: Wear resistance: tested in accordance with GB / T3810.7-2016; Antibacterial property: Tested according to the method disclosed in JC / T897-2014 (the bacteria species is Escherichia coli).

[0041] Table 1: It can be seen from Table 1 that by comparing Example 1 with Control Example 1, the doping of Zn can significantly improve the visual performance of sanitary ceramics. By comparing Example 1 with Control Example 2, the phytic acid-Ce 3+ and Cu 2+ Compared with phytic acid-Cu 2+ , and the antibacterial performance is more excellent. By comparing Example 1 with Control Examples 3-4, it can be seen that phytic acid is beneficial to promoting the improvement of antibacterial performance and wear resistance, and Ni 0.96 Zn 0.04 Co2O4 and phytic acid-Ce 3+ and Cu 2+ There is a mutual promotion effect between them, which jointly promotes the improvement of the antibacterial property and mechanical property of sanitary ceramics. In addition, the sanitary ceramics prepared by the present invention are easy to clean and have a flat and smooth surface.

[0042] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. An antibacterial and easy-to-clean sanitary ceramic, characterized in that: The antibacterial and easy-to-clean sanitary ceramics include a sanitary ceramic body and a glaze layer. The glaze layer includes the following raw materials in parts by weight: Kaolin 70~90 parts, baddeleyite 10~30 parts, feldspar 20~40 parts, dolomite 5~15 parts, Ni 1-x Zn x Co2O4, x = 0.03~0.05, 4~8 parts; phytic acid-Ce 3+ and Cu 2+ 6-12 parts of composite material, 4-12 parts of polyvinyl alcohol, and 50-70 parts of water.

2. The antibacterial and easy-to-clean sanitary ceramic according to claim 1, characterized in that: The particle sizes of the kaolin, baddeleyite, potassium feldspar and dolomite are all 30-70 μm.

3. The antibacterial and easy-to-clean sanitary ceramic according to claim 1, characterized in that: The Ni 1-x Zn x The preparation method of Co2O4 comprises the following steps: Nickel salt, zinc salt, cobalt salt and polyethylene glycol 2000 are added to ethylene glycol, ultrasonically dispersed for a certain period of time, and then subjected to solvent thermal reaction, cooled to room temperature, filtered, washed, dried, then ground and calcined to obtain Ni 1-x Zn x Co2O4.

4. The antibacterial and easy-to-clean sanitary ceramic according to claim 3, characterized in that: The nickel salt is one of nickel nitrate, nickel chloride and nickel acetate; the zinc salt is one of zinc nitrate, zinc chloride and zinc acetate; the cobalt salt is one of cobalt nitrate, cobalt chloride and cobalt acetate; the ratio of the nickel salt, zinc salt, cobalt salt and polyethylene glycol 2000 is (1-x) mol: x mol: 2 mol, 200-240 g, x=0.03-0.

05.

5. The antibacterial and easy-to-clean sanitary ceramic according to claim 3, characterized in that: The ultrasonic dispersion time is 20-40 minutes; the solvent thermal reaction condition is solvent thermal reaction at 160-200° C. for 10-20 hours.

6. The antibacterial and easy-to-clean sanitary ceramic according to claim 3, characterized in that: The drying step is performed at 60-100° C. for 10-14 hours; and the calcining step is performed at 280-320° C. for 2-4 hours.

7. The antibacterial and easy-to-clean sanitary ceramic according to claim 1, characterized in that: The phytic acid-Ce 3+ and Cu 2+ The method for preparing the composite material comprises the following steps: Sodium phytate, cerium salt and copper salt were ultrasonically dispersed in deionized water, stirred at room temperature for a certain period of time, filtered, washed and vacuum dried to obtain phytic acid-Ce 3+ and Cu 2+ Composite materials.

8. The antibacterial and easy-to-clean sanitary ceramic according to claim 7, characterized in that: The molar ratio of the sodium phytate, cerium salt and copper salt is 1:0.04-0.08:0.6-0.8, the cerium salt is one of cerium nitrate, cerium chloride and cerium acetate; the copper salt is one of copper nitrate, copper chloride and copper acetate.

9. The antibacterial and easy-to-clean sanitary ceramic according to claim 7, characterized in that: The stirring time is 2-4 hours; the vacuum drying is performed at 60-80° C. for 14-20 hours.

10. A method for preparing an antibacterial and easy-to-clean sanitary ceramic according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: 1) Preparation of bathroom ceramic embryos: 2) Place kaolin, baddeleyite, feldspar, dolomite and water in a ball mill and mix at a speed of 400-600 r / min for 2-6 hours; 3) Then Ni 1-x Zn x Co2O4, Phytate-Ce 3+ and Cu 2+ The composite material and polyethylene glycol are added into the ball mill and ball milling is continued for 10 to 30 minutes to obtain a glaze; 4) applying the glaze to the surface of the sanitary ware ceramic body in step 1), and drying naturally to obtain a glazed sanitary ware ceramic body; 5) The glazed sanitary ceramic body is heated from room temperature to 500-600° C. at a heating rate of 1-3° C. and kept at that temperature for 2-6 hours, then heated to 1200-1400° C. at a heating rate of 10-14° C. and sintered for 4-8 hours; cooled to 600-800° C. and kept at that temperature for 4-8 hours; and then cooled in the furnace to obtain an antibacterial and easy-to-clean sanitary ceramic body.

Citation Information

Patent Citations

  • Antibacterial bathroom ceramic article and preparation method thereof

    CN106673633A